2021
DOI: 10.1099/mgen.0.000571
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of beta-lactam-resistant Escherichia coli from Australian fruit bats indicates anthropogenic origins

Abstract: Antimicrobial-resistant Escherichia coli , particularly those resistant to critically important antimicrobials, are increasingly reported in wildlife. The dissemination of antimicrobial-resistant bacteria to wildlife indicates the far-reaching impact of selective pressures imposed by humans on bacteria through misuse of antimicrobials. The grey-headed flying fox (GHFF; Pteropus poliocephalus), a fruit bat endemic to eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 91 publications
(221 reference statements)
1
37
1
Order By: Relevance
“…Nonetheless, investigations of urban gulls and pigeons repeatedly produced Escherichia coli and Salmonella enterica that carry genes encoding resistance to fluoroquinolones, carbapenems and extended spectrum β-lactams [ 27 , 28 , 29 , 30 , 31 ]. In Australia, MDR E. coli have also been recovered from penguins [ 32 ] and bats [ 33 ], indicating that enterobacterial flora carried by wildlife species that intersect with human populations readily harbor ARG combinations that mirror those circulating in veterinary and human clinical environments. The sul3 gene has been reported globally and often in association with E. coli sourced from intensive animal production but also frequently in humans [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, investigations of urban gulls and pigeons repeatedly produced Escherichia coli and Salmonella enterica that carry genes encoding resistance to fluoroquinolones, carbapenems and extended spectrum β-lactams [ 27 , 28 , 29 , 30 , 31 ]. In Australia, MDR E. coli have also been recovered from penguins [ 32 ] and bats [ 33 ], indicating that enterobacterial flora carried by wildlife species that intersect with human populations readily harbor ARG combinations that mirror those circulating in veterinary and human clinical environments. The sul3 gene has been reported globally and often in association with E. coli sourced from intensive animal production but also frequently in humans [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…are multiple reports of IS26 class 1 integron variants in E. coli from animals in Australia, including cows and pigs [18,51,52] and Grey-headed flying foxes (Pteropus poliocephalus) [53], as well as in human clinical cases [54]. The presence of class 1 integrons with IS26 variants in E. coli isolates from free-ranging A. p. doriferus pups provides further evidence to suggest that this colony is exposed to a marine environment that is contaminated by various sources of anthropogenic pollution.…”
Section: Plos Onementioning
confidence: 72%
“…The occurrence of five clinically relevant representatives belonging to international high-risk clonal lineages among only 12 ESBL-producing strains is remarkable. ST131 has not only been reported as the major E. coli clone in the clinical setting [ 32 ] but is often also found in veterinary, food, and environmental settings [ 52 , 53 ]. While previous studies have frequently found MDR ST58 strains in farm animals and, to a lesser extent, in wild birds [ 54 , 55 ] and as contaminants of retail meat [ 21 ], ST38 has been detected in several animal species, including broilers, rats, and black-headed gulls [ 12 , 56 ], with the latter matching our results.…”
Section: Discussionmentioning
confidence: 99%